Il molteplice umano (Itinera, 2025)
The article then examines how modern notions of human omnipotence persist and are reinforced by digital technologies, and argues for a shift toward new forms of interaction between humans and technological artefacts. Instead of domination or complete delegation, these relations should take the form of mobile, negotiated exchanges that preserve difference and enable creativity.